Fabric and preparation method thereof

By using protease to modify polyamide fibers under acidic conditions, combined with the finishing technology of polyalkylsiloxane hydrosol, the problem of insufficient modification effect is solved, and efficient modification and persistent finish of fibers are achieved. The effect improves the hydrophilicity and antibacterial properties of the fiber.

CN113930973BActive Publication Date: 2025-02-11WUJIANG FUHUA WEAVING
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202111272638.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-02-11
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

When modifying polyamide fibers, the modification effect is not long-lasting, and the amide bond hydrolysis rate is slow, which affects the hydrophilicity and dyeing properties of the fibers.

Method used

Under acidic conditions, the surface modification of the fibers is used to form carboxyl groups and form microscopic rough structures. Then, the modified fibers are sorted with polyalkylsiloxane hydrosol, which is improved through the dual effect of mechanical nail anchors and valence bonds. The durability of the finishing effect.

Benefits of technology

The durability and efficiency of fiber surface modification are improved, the hydrophilicity and dyeing performance of fibers are improved, and the antibacterial function is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003328399330000131
    Figure BDA0003328399330000131
  • Figure BDA0003328399330000141
    Figure BDA0003328399330000141
  • Figure HDA0003328399340000011
    Figure HDA0003328399340000011
Patent Text Reader

Abstract

The invention discloses a method for preparing a fabric, comprising the following steps: surface-modifying the fiber of the fabric by using a protease under acidic conditions; then preparing a polyalkylsiloxane hydrosol; finishing the modified fabric by using the polyalkylsiloxane hydrosol to obtain the fabric; the surfactant used in the process of preparing the polyalkylsiloxane hydrosol is a mixture of sodium dodecylbenzene sulfonate and twain-80. The fiber used for the fabric is aliphatic polyamide fiber. The fabric preparation method of the invention controls the pH value of the system to always be 3.0-4.0 and adds a nonionic surfactant, so that the protease efficiently plays a role in modifying the fiber, thereby generating a synergistic effect; at the same time, a microscopic rough structure is formed on the fiber surface by an erosion effect, and the durability of the finishing effect is improved by the dual effects of mechanical anchoring and valence bond combination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textiles, and in particular to a method for preparing a multifunctional polyamide fabric and the multifunctional fabric prepared by the preparation method. Background Art

[0002] With the development of science and technology and the improvement of living standards, people are increasingly pursuing an environmentally friendly, healthy and safe life. Functional textiles have gradually become the trend of textile development today. Functional textiles refer to textiles with some special functions that are different from the inherent properties of ordinary textiles. According to different performances and uses, functional textiles can be mainly divided into hygienic and environmental protection functions, protective functions, medical care functions, thermal and humidity comfort functions, etc.

[0003] Sol-gel technology refers to the process of using solutions, sol-gel and heat treatment to form functional films of different components on the surface of a substrate using compounds containing highly active chemical components, so as to improve the physical and mechanical properties of textiles (such as wear resistance), antistatic properties, anti-stickiness, flame retardancy and other functional properties. Among them, polyalkylsiloxane hydrosol refers to a reactive functional material formed by the hydrolysis and condensation reaction of alkylsiloxane, which can form a functional film on the fiber surface through valence bond bonding and silanol (Si-OH), thereby giving textiles functional properties.

[0004] When polyalkylsiloxane is used to modify polyamide fibers, not only the amount of polyalkylsiloxane fixation is reduced due to the hydrophobicity of the fiber surface, but also the durability of the modification effect is affected due to the small number of active reactive groups on the fiber surface. Theoretical analysis shows that constructing a rough structure on the surface of polyamide fibers and generating active reactive groups through modification is one of the effective methods to improve the modification effect of polyalkylsiloxane.

[0005] At present, the methods for surface modification of polyamide fibers mainly include concentrated acid or concentrated alkali hydrolysis method (such as the relevant contents disclosed in patents such as application numbers 201010218397.3, 202010654281.8, and 202010654275.2), plasma method and electron beam irradiation method. Among them, the acid or alkali hydrolysis method often causes serious damage to the fiber strength due to the difficulty in controlling the treatment conditions. The plasma method and electron beam irradiation method have not yet been well implemented in large-scale production and application.

[0006] Bioenzymes are widely used in textile finishing due to their high efficiency, specificity and mild treatment conditions. Literature reports that proteases, cutinases, amidases and lipases have a hydrolytic effect on the amide bond (-COONH-) in polyamides, but the catalytic activity of enzymes on polyamide polymers is not high, the treatment time is too long, and the improvement of the hydrophilicity, dyeing and other related properties of the modified fibers is not ideal. In addition, due to surface erosion, bioenzyme treatment will also cause certain damage to the fiber strength.

[0007] For example, in the Chinese invention patent application with application number 200580018511.5 and titled Method for Modifying Polyamide, a modification treatment of polyamide using protease is disclosed. However, the content disclosed in the application mainly includes increasing the carboxyl (-COOH) content on the surface of polyamide fiber by protease modification, thereby improving the hydrophilicity and dyeing properties of the fiber; and in the treatment method disclosed in the application, only salt (sodium phosphate and sodium citrate) is used to adjust the pH value of the enzyme reaction solution, and no other additives are added. The disadvantage is that the hydrolysis rate of the amide bond is slow, and it often takes 24 hours or longer to react to obtain a sample with a significantly increased carboxyl content. Summary of the invention

[0008] In view of this, in order to overcome the defects of the prior art, an object of the present invention is to provide a method for preparing a fabric that can maintain properties more durable and effectively.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] A method for preparing fabrics, comprising the following steps: using protease to modify the surface of fabric fibers under acidic conditions; then preparing polyalkylsiloxane hydrosol; using the polyalkylsiloxane hydrosol to finish the modified fabric to obtain the fabric; the surfactant used in the process of preparing the polyalkylsiloxane hydrosol is a mixture of sodium dodecylbenzene sulfonate and TWAIN-80. The fibers used in the fabrics are aliphatic polyamide fibers.

[0011] According to some preferred embodiments of the present invention, the acidic condition has a pH value of 3.0-4.0, preferably 3.5.

[0012] According to some preferred embodiments of the present invention, a surfactant is used in the process of modifying the fibers of the fabric, wherein the surfactant is a nonionic surfactant, preferably a nonylphenol polyoxyethylene ether and aliphatic polyoxyethylene ether surfactants.

[0013] According to some preferred embodiments of the present invention, a buffer solution is used in the process of modifying the fibers of the fabric, and the buffer solution is composed of a mixture of 0.1-0.3 mol / L disodium hydrogen phosphate and 0.0.5-0.2 mol / L citric acid. Preferably, the buffer solution is composed of a mixture of 0.2 mol / L disodium hydrogen phosphate and 0.1 mol / L citric acid in a volume ratio of 3:7, so that the pH value of the system is maintained at about 3.5.

[0014] The principle of fiber surface modification is as follows: the fiber surface is modified by hydrolyzing the amide bond (-COONH-) to generate carboxyl groups (-COOH) that can react with the silanol (-Si-OH) on the surface of the silica hydrosol particles. At the same time, a microscopic rough structure is formed on the fiber surface through the stripping effect, and the durability of the finishing effect is improved through the dual effects of mechanical anchoring and valence bond combination; the optimal application pH value for acid protease to modify the polyamide fiber surface is about 3.5, and both acid and protease can hydrolyze the amide bond (-COONH-) in the molecular structure of polyamide fibers to generate A synergistic effect can be produced in the process of forming amino groups (-NH2) and carboxyl groups (-COOH); adjusting the pH with a buffer solution can effectively neutralize the carboxyl groups (-COOH) generated during the modification process, so that the pH value of the system is always maintained at around 3.5 to ensure the highest effectiveness of the protease; organic acids are more moderate in hydrolyzing amide bonds than inorganic strong acids, and the conditions are easy to control; adding non-ionic surfactants can improve the wettability of the fiber surface, accelerate fiber swelling, and thereby improve the spreading of the bio-enzyme treatment solution on the fiber surface, thereby increasing the modification efficiency by increasing the effective contact area between the bio-enzyme and the fiber surface.

[0015] According to some preferred embodiments of the present invention, the pH value of deionized water is adjusted to 3.0-4.0 with a buffer solution, and then a surfactant and a protease are added, wherein the amount of the surfactant is 1-1.5 times the critical micelle concentration (CMC), and the concentration of the protease in the system is 0.02-2.0 g / mL; the fabric is treated at a bath ratio of 1:10-35, and then the fabric is washed and dried.

[0016] The nonionic surfactant added in the process of protease modification of polyamide fiber can not only improve the wettability of fiber, but also improve the swelling performance of fiber, and increase the effective contact area between protease and fiber surface, so as to improve the treatment efficiency. Meanwhile, the main purpose of the present invention is to generate more carboxyl groups and form microscopic rough structure on the fiber surface through protease modification, and improve the fixing strength of the finishing agent on the fiber surface by combining the dual effects of valence bond binding and mechanical anchoring when the silica hydrosol-based antibacterial agent is used for finishing.

[0017] In some embodiments of the present invention, the specific steps of fiber surface modification are as follows: adjust the pH value of 1L deionized water to 3.5 with 20mL buffer solution, then add surfactant and 0.2-2.0g protease, the amount of surfactant is 1-1.5 times of CMC, treat the fabric at 40℃ for 2-6h, and the bath ratio is 1:30. After treatment, inactivate at 60℃ for 10min, take out the fabric, wash with water and dry.

[0018] According to some preferred implementation aspects of the present invention, the protease is papain, and the optimal application pH value of papain is 3.0-4.0. The acidity of this pH value will not have a significant effect on fiber damage, and can produce a synergistic effect with biological enzymes.

[0019] According to some preferred implementation aspects of the present invention, the surfactant is a mixture of sodium dodecylbenzene sulfonate and twain-80 in a mass ratio of 1:0.1-0.3.

[0020] According to some preferred embodiments of the present invention, the preparation of the polyalkylsiloxane hydrosol comprises the following steps: adding hydrochloric acid to deionized water, then adding a surfactant and a defoaming agent, stirring to fully dissolve and mix the surfactant, adding alkylsiloxane while stirring, and after the alkylsiloxane is added, continuing to stir and heating to 40-60° C., reacting for 30-60 minutes under stirring to obtain the polyalkylsiloxane hydrosol.

[0021] In some embodiments of the present invention, the preparation steps of the polyalkylsiloxane hydrosol are as follows: under the condition of 25-30°C, 3-6mL of hydrochloric acid is added to 1L of deionized water, and then 1-2g of a surfactant and 0.1-0.3g of a defoaming agent are added, and the mixture is stirred at a speed of 300r / min to fully dissolve the sodium dodecylbenzene sulfonate, and the stirring speed is adjusted to 600-1000r / min. Within 5-10min, 20-40g of alkylsiloxane is added while stirring. After the alkylsiloxane is added, stirring is continued for 60-90min, and then the temperature is increased to 40-60°C at a heating rate of 1-2°C / min, and the mixture is reacted for 30-60min under stirring to obtain a polyalkylsiloxane hydrosol.

[0022] The principle of this step is: using a mixture of anionic sodium dodecylbenzene sulfonate and non-ionic twain-80 as a surfactant, because the addition of twain-80 will not change the charge of the hydrosol system, but can enhance the strength of the sodium dodecylbenzene sulfonate micelles, and at the same time can effectively reduce the viscosity of the hydrosol, thereby improving the stability of the hydrosol and the uniformity of the particle size; the addition of the defoamer can effectively prevent the surfactant from generating foam under high-speed stirring conditions, thereby avoiding affecting the dispersibility of the alkyl siloxane and affecting the final effect.

[0023] Preferably, the alkylsiloxane is one or more selected from methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, and γ-aminopropyltriethoxysilane.

[0024] According to some preferred implementation aspects of the present invention, an antibacterial agent is further added during the preparation of the polyalkylsiloxane hydrosol, and the antibacterial agent is a chitosan / micron elemental silver composite antibacterial agent.

[0025] In some embodiments of the present invention, the preparation method of the hydrosol with antibacterial function is as follows: add a surfactant with a mass concentration of 0.1% and a defoamer with a mass concentration of 0.01% to a deionized hydrochloric acid solution with a mass concentration of 0.46%, stir at a speed of 300r / min for 60min under a temperature of 25°C, and after sodium dodecylbenzene sulfonate is fully dissolved, add a chitosan / micron elemental silver composite antibacterial agent with a mass ratio of 15% to alkyl siloxane, continue stirring for 60min to make the antibacterial agent evenly dispersed, add a 4% alkyl siloxane within 5min under a stirring condition of 600r / min, and continue stirring for 60min after the alkyl siloxane is added, and then heat to 60°C at a heating rate of 2°C / min, react for 30min under stirring conditions, and obtain a SiO2 hydrosol-based chitosan / micron elemental silver composite antibacterial agent. The mass concentration of the present invention is the mass concentration of the corresponding substance in the formed solution, not the original concentration of the added substance.

[0026] In some embodiments of the present invention, the preparation of chitosan / micron elemental silver composite antibacterial agent comprises the following steps:

[0027] 1) Preparation of chitosan solution: Add chitosan with a mass concentration of 2-5% and acetic acid with a mass concentration of 1.0-2.0% into 200 mL of deionized water. The deacetylation degree of the chitosan used is ≥90%.

[0028] 2) preparing a micron elemental silver dispersion: adding 0.1-0.2% sodium dodecylbenzene sulfonate and 2-5 mL ethanol into 50 mL deionized water, stirring at a speed of 300 r / min, after the sodium dodecylbenzene sulfonate is completely dissolved, adding 5-10% of the mass weight of chitosan to the micron elemental silver while stirring, precipitating a micron elemental silver crude product with a centrifuge, and then washing with deionized water for 3-5 times to obtain micron elemental silver.

[0029] 3) Preparation of composite antibacterial agent: at 25-30°C, stir at a speed of 600r / min, slowly add the micron elemental silver dispersion into the chitosan solution within 10-20min, after the addition is complete, continue stirring for 120-240min, use a centrifuge to precipitate the crude chitosan / micron elemental silver composite antibacterial agent, then wash with deionized water for 3-5 times, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

[0030] In some embodiments of the present invention, the preparation of micron elemental silver comprises the following steps: adding polyvinyl pyrrolidone with a mass concentration of 0.5-1.0% and a reducing agent with a mass concentration of 1-2% to 200 mL of deionized water at 25-30°C, stirring at a speed of 300 r / min, and after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjusting the pH of the reaction solution to 3-4 with an acetic acid-sodium acetate buffer solution, slowly adding silver nitrate with a mass concentration of 2-5% within 5-10 minutes under stirring, continuing to stir for 10-20 minutes after the addition, and then heating to 40-50°C at a speed of 1-2°C / min, reacting at a constant temperature for 30-60 minutes, precipitating the micron elemental silver crude product with a centrifuge, and then washing with deionized water 3-5 times, and filtering to obtain micron elemental silver with a particle size of 1-20 μm.

[0031] The reducing agent used in the preparation process of micron elemental silver is one of trisodium citrate and ascorbic acid or a complex of the two.

[0032] According to some preferred embodiments of the present invention, finishing the modified fabric comprises the following steps: adjusting the pH value of the polyalkylsiloxane hydrosol to 6-7 with an alkali agent, finishing the modified fabric by a padding method, and then washing and drying to produce the fabric.

[0033] According to some preferred embodiments of the present invention, the alkali agent refers to a sodium hydroxide solution with a mass concentration of 4-8 g / L.

[0034] In some embodiments of the present invention, the steps of polyalkylsiloxane finishing of modified fabrics are as follows: at 25-30°C, the pH value of the polyalkylsiloxane hydrosol is adjusted to 6-7 with an alkali agent, and the modified polyamide fabric is finished by a two-immersion and two-rolling method with a rolling rate of 60-100%, and then dried at a temperature of 80-90°C for 2-5 minutes, and then baked at a temperature of 140-160°C for 3-6 minutes, washed with water, and finally dried at a temperature of 80-100°C to make a multifunctional polyamide fabric.

[0035] The principle of this step is that polyamide fibers are easily hydrolyzed under acidic conditions, which in turn affects the performance of the fabric. Adjusting the pH value of the silica sol to 6-7 will neither cause rapid condensation of the sol particles nor significantly affect the fiber strength.

[0036] The present invention also provides a fabric prepared by the above-mentioned preparation method.

[0037] Due to the adoption of the above technical scheme, compared with the prior art, the advantages of the present invention are as follows: the fabric preparation method of the present invention, by controlling the pH value of the system to always be 3.0-4.0 and adding a non-ionic surfactant, allows the protease to efficiently play its role in modifying the fiber, thereby producing a synergistic effect; at the same time, a microscopic rough structure is formed on the fiber surface through the stripping effect, and the durability of the finishing effect is improved through the dual effects of mechanical anchoring and valence bond combination; a mixture of anionic sodium dodecylbenzene sulfonate and non-ionic twain-80 is used as a surfactant to enhance the strength of the sodium dodecylbenzene sulfonate micelles, and at the same time, the viscosity of the hydrosol can be effectively reduced, thereby improving the stability of the hydrosol and the uniformity of the particle size. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0039] Figure 1 This is a microscopic magnified image of the original polyamide fiber used in the preferred embodiment of the present invention;

[0040] Figure 2 This is a microscopic enlarged picture of the polyamide fiber after bioenzyme modification in the preferred embodiment 1-1 of the present invention;

[0041] Figure 3 This is a comparison picture of the antibacterial effect of the fabrics prepared by the preferred embodiment 3-1 of the present invention and comparative examples 1-4 to 1-7. DETAILED DESCRIPTION

[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0043] Example 1-1 Fiber surface modification

[0044] Use 20mL buffer solution to adjust the pH value of 1L deionized water to 3.5, the optimal application value of protease, and then add 1.0g protease and 1.2CMC nonylphenol polyoxyethylene ether, and treat at 40℃ for 3h, with a bath ratio of 1:30. After treatment, inactivate at 60℃ for 10min, take out the fabric, wash it with water, and dry it.

[0045] Example 1-2 Fiber surface modification

[0046] Use 20mL buffer solution to adjust the pH value of 1L deionized water to 3.5, the optimal application value of protease, and then add 1.5g protease and 1.2CMC nonylphenol polyoxyethylene ether, and treat at 40℃ for 2h, with a bath ratio of 1:35. After treatment, inactivate at 60℃ for 10min, take out the fabric, wash it with water, and dry it.

[0047] Example 1-3 Fiber surface modification

[0048] Use 20mL buffer solution to adjust the pH value of 1L deionized water to 3.5, the optimal application value of protease, and then add 1.0g protease and 1.2CMC nonylphenol polyoxyethylene ether, and treat at 40℃ for 3h, with a bath ratio of 1:25. After treatment, inactivate at 60℃ for 10min, take out the fabric, wash it with water, and dry it.

[0049] Example 2-1 Preparation of hydrosol with antibacterial function

[0050] 1. Preparation of micron-sized elemental silver

[0051] At 25°C, add 0.7% polyvinyl pyrrolidone and 1% reducing agent to 200 mL deionized water, stir at 300 r / min, after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjust the pH of the reaction solution to 3-4 with acetic acid-sodium acetate buffer solution, slowly add 3% silver nitrate within 8 minutes under stirring, continue stirring for 15 minutes after the addition, then heat to 40°C at a speed of 1.5°C / min, react at constant temperature for 50 minutes, precipitate elemental silver with a centrifuge, wash with deionized water 5 times, and obtain micron elemental silver by suction filtration.

[0052] 2. Preparation of chitosan / micronized silver composite antibacterial agent

[0053] Chitosan solution: chitosan with a mass concentration of 3% and acetic acid with a mass concentration of 1.0% were added to 200 mL of deionized water to dissolve.

[0054] Micron elemental silver dispersion: add 0.15% surfactant and 3mL ethanol into 50mL deionized water, stir at 300r / min, after sodium dodecylbenzene sulfonate is completely dissolved, add 6% micron elemental silver to the mass of chitosan while stirring.

[0055] At 25°C, stir at 600 r / min and slowly add the micron elemental silver dispersion into the chitosan solution within 10 min. After the addition is complete, continue stirring for 150 min. Use a centrifuge to precipitate the elemental silver, wash it with deionized water 5 times, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

[0056] 3. Preparation of SiO2 hydrosol-based antibacterial agent

[0057] A surfactant with a mass concentration of 0.1% and a defoamer with a mass concentration of 0.01% are added to a deionized hydrochloric acid solution with a mass concentration of 0.46%, and stirred at a speed of 300r / min for 60min under a temperature of 25°C. After sodium dodecylbenzene sulfonate is fully dissolved, a chitosan / micron elemental silver composite antibacterial agent with a mass ratio of 15% to alkylsiloxane is added, and stirring is continued for 60min to make the antibacterial agent uniformly dispersed, and methyltrimethoxysilane with a mass concentration of 4% is added within 5min under a stirring condition of 600r / min. After the precursor is added, stirring is continued for 60min, and then the temperature is raised to 60°C at a heating rate of 2°C / min, and the reaction is carried out under stirring for 30min to obtain a SiO2 hydrosol-based antibacterial agent. The surfactant is a mixture of sodium dodecylbenzene sulfonate and twain-80 with a mass ratio of 1:0.2.

[0058] Example 2-2 Preparation of hydrosol with antibacterial function

[0059] 1. Preparation of micron-sized elemental silver

[0060] At 25° C., add 0.5% polyvinyl pyrrolidone and 1.5% reducing agent to 200 mL deionized water, stir at 300 r / min, after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjust the pH of the reaction solution to 3-4 with acetic acid-sodium acetate buffer solution, slowly add 5% silver nitrate within 8 minutes under stirring, continue stirring for 15 minutes after the addition, then heat to 40° C. at a speed of 1.5° C. / min, react at constant temperature for 30 minutes, precipitate elemental silver with a centrifuge, wash with deionized water 5 times, and obtain micron elemental silver by suction filtration.

[0061] 2. Preparation of chitosan / micronized silver composite antibacterial agent

[0062] Chitosan solution: chitosan with a mass concentration of 3% and acetic acid with a mass concentration of 1.0% were added to 200 mL of deionized water to dissolve.

[0063] Micron elemental silver dispersion: add 0.15% surfactant and 3mL ethanol into 50mL deionized water, stir at 300r / min, after sodium dodecylbenzene sulfonate is completely dissolved, add 10% micron elemental silver to the mass of chitosan while stirring.

[0064] At 25°C, stir at a speed of 600 r / min and slowly add the micron elemental silver dispersion into the chitosan solution within 10 minutes. After the addition is complete, continue stirring for 200 minutes, use a centrifuge to precipitate the elemental silver, wash it with deionized water for 5 times, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

[0065] 3. Preparation of SiO2 hydrosol-based antibacterial agent

[0066] The surfactant with a mass concentration of 0.16% and the defoamer with a mass concentration of 0.016% are added to a deionized hydrochloric acid solution with a mass concentration of 0.5%, and stirred at a speed of 300r / min for 60min under the condition of a temperature of 25°C. After the sodium dodecylbenzene sulfonate is fully dissolved, a chitosan / micron elemental silver composite antibacterial agent with a mass ratio of 20% to alkylsiloxane is added, and the stirring is continued for 90min to make the antibacterial agent uniformly dispersed, and propyltrimethoxysilane with a mass concentration of 4% is added within 5min under the stirring condition of 600r / min. After the precursor is added, the stirring is continued for 60min, and then the temperature is raised to 40°C at a heating rate of 1.5°C / min, and the reaction is carried out for 30min under stirring to obtain a SiO2 hydrosol-based antibacterial agent. The surfactant is a mixture of sodium dodecylbenzene sulfonate and twain-80 with a mass ratio of 1:0.3.

[0067] Example 2-3 Preparation of hydrosol with antibacterial function

[0068] 1. Preparation of micron-sized elemental silver

[0069] At 25° C., add 0.7% polyvinyl pyrrolidone and 1% reducing agent to 200 mL deionized water, stir at 300 r / min, after the polyvinyl pyrrolidone and the reducing agent are completely dissolved, adjust the pH of the reaction solution to 3-4 with acetic acid-sodium acetate buffer solution, slowly add 4% silver nitrate within 10 minutes under stirring, continue stirring for 15 minutes after the addition, then heat to 40° C. at a speed of 1.5° C. / min, react at constant temperature for 40 minutes, precipitate elemental silver with a centrifuge, wash with deionized water 5 times, and obtain micron elemental silver by suction filtration.

[0070] 2. Preparation of chitosan / micronized silver composite antibacterial agent

[0071] Chitosan solution: chitosan with a mass concentration of 3% and acetic acid with a mass concentration of 1.0% were added to 200 mL of deionized water to dissolve.

[0072] Micron elemental silver dispersion: add 0.1% surfactant and 3mL ethanol into 50mL deionized water, stir at 300r / min, after sodium dodecylbenzene sulfonate is completely dissolved, add 8% micron elemental silver to the mass of chitosan while stirring.

[0073] At 25°C, stir at 600 r / min and slowly add the micron elemental silver dispersion into the chitosan solution within 10 min. After the addition is complete, continue stirring for 150 min. Use a centrifuge to precipitate the elemental silver, wash it with deionized water 5 times, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

[0074] 3. Preparation of SiO2 hydrosol-based antibacterial agent

[0075] The surfactant with a mass concentration of 0.13% and the defoamer with a mass concentration of 0.013% are added to a deionized hydrochloric acid solution with a mass concentration of 0.46%, and stirred at a speed of 300r / min for 60min under the condition of a temperature of 25°C. After sodium dodecylbenzene sulfonate is fully dissolved, a chitosan / micron elemental silver composite antibacterial agent with a mass ratio of 20% to alkyl siloxane is added, and stirring is continued for 60min to make the antibacterial agent uniformly dispersed, and an alkyl siloxane with a mass concentration of 4% (the mass ratio of methyl trimethoxy silane to propyl trimethoxy silane is 3:1) is added within 5min under the stirring condition of 600r / min. After the precursor is added, stirring is continued for 60min, and then the temperature is raised to 40°C at a heating rate of 2°C / min, and the reaction is carried out for 40min under stirring to obtain a SiO2 hydrosol-based antibacterial agent. The surfactant is a mixture of sodium dodecylbenzene sulfonate and twain-80 with a mass ratio of 1:0.1.

[0076] Examples 2-1 to 2-3 provide a method for preparing a multifunctional composite antibacterial finishing agent, which has the following advantages: simple process, stable and easy-to-control process parameters; the antibacterial finishing agent has excellent antibacterial effect; it has active groups that can form valence bonds with the fiber surface, and the antibacterial effect of the finished fabric is long-lasting; the finishing agent can simultaneously give the finished fabric good antibacterial and antibacterial properties, water repellency and soft feel.

[0077] Example 3-1 Preparation of fabric

[0078] The preparation method of the multifunctional fabric in this embodiment specifically includes the following steps:

[0079] (1) Fiber surface modification: The polyamide fabric is modified by the fiber surface modification method in Example 1-1;

[0080] (2) Preparation of composite antibacterial finishing agent: The SiO2 hydrosol-based chitosan / micron elemental silver composite antibacterial agent was prepared by the preparation method in Example 2-1.

[0081] (3) Finishing of modified fabric with polyalkylsiloxane: At 25°C, the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) is adjusted to 6-7 with an alkali agent, and the modified polyamide fabric in step (1) is finished by a double dipping and double rolling method with a rolling rate of 80%, followed by drying at 80°C for 2 min, and then baking at 140°C for 3 min, washing with water, and finally drying at 80°C to produce a multifunctional polyamide fabric.

[0082] Example 3-2 Preparation of fabric

[0083] The preparation method of the multifunctional fabric in this embodiment specifically includes the following steps:

[0084] (1) Fiber surface modification: The polyamide fabric is modified by the fiber surface modification method in Example 1-2;

[0085] (2) Preparation of composite antibacterial finishing agent: The SiO2 hydrosol-based chitosan / micron elemental silver composite antibacterial agent was prepared by the preparation method in Example 2-2.

[0086] (3) Finishing of modified fabric with polyalkylsiloxane: At 25°C, the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) is adjusted to 6-7 with an alkali agent, and the modified polyamide fabric in step (1) is finished by a double dipping and double rolling method with a rolling rate of 80%, followed by drying at 80°C for 2 min, and then baking at 140°C for 3 min, washing with water, and finally drying at 80°C to produce a multifunctional polyamide fabric.

[0087] Example 3-3 Preparation of fabric

[0088] The preparation method of the multifunctional fabric in this embodiment specifically includes the following steps:

[0089] (1) Fiber surface modification: The polyamide fabric is modified by the fiber surface modification method in Examples 1-3;

[0090] (2) Preparation of composite antibacterial finishing agent: The SiO2 hydrosol-based chitosan / micron elemental silver composite antibacterial agent was prepared by the preparation method in Example 2-3.

[0091] (3) Finishing of modified fabric with polyalkylsiloxane: At 25°C, the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) is adjusted to 6-7 with an alkali agent, and the modified polyamide fabric in step (1) is finished by a double dipping and double rolling method with a rolling rate of 80%, followed by drying at 80°C for 2 min, and then baking at 140°C for 3 min, washing with water, and finally drying at 80°C to produce a multifunctional polyamide fabric.

[0092] Examples 3-1 to 3-3 provide a method for preparing a multifunctional polyamide fabric, which has the following advantages: the process is simple, and the process parameters are stable and easy to control; the fabric has excellent hydrophobicity, antistatic properties and a comfortable feel; the fabric has long-lasting antibacterial properties and good washability.

[0093] Comparative Example 1-1

[0094] The difference between this comparative example and Example 1-1 is that in the fiber surface modification method of this comparative example, when protease is used for modification, no nonionic surfactant is added. The remaining steps of this comparative example are basically the same as those of Example 1-1.

[0095] Comparative Example 1-2

[0096] The difference between this comparative example and Example 1-1 is that the pH value of the control system in the fiber surface modification method of this comparative example is 4.2. The remaining steps of this comparative example are basically the same as those of Example 1-1.

[0097] Comparative Examples 1-3

[0098] The difference between this comparative example and Example 1-1 is that the pH value of the control system in the fiber surface modification method of this comparative example is 2.8. The remaining steps of this comparative example are basically the same as those of Example 1-1.

[0099] Comparative Examples 1-4

[0100] The difference between this comparative example and Example 3-1 is that in this comparative example, when preparing the SiO2 hydrosol-based antibacterial agent, micron elemental silver is used to replace the chitosan / micron elemental silver composite antibacterial agent, and the remaining steps of this comparative example are basically the same as those of Examples 2-1 and Example 3-1.

[0101] Comparative Examples 1-5

[0102] The difference between this comparative example and Example 3-1 is that in this comparative example, when preparing the SiO2 hydrosol-based antibacterial agent, nano-elemental silver is used to replace the chitosan / micron elemental silver composite antibacterial agent, and the remaining steps of this comparative example are basically the same as those of Examples 2-1 and Example 3-1.

[0103] Comparative Examples 1-6

[0104] The difference between this comparative example and Example 3-1 is that in this comparative example, chitosan is used to replace the chitosan / micron elemental silver composite antibacterial agent when preparing the SiO2 hydrosol-based antibacterial agent, and the remaining steps of this comparative example are basically the same as those of Examples 2-1 and Example 3-1.

[0105] Comparative Examples 1-7

[0106] The difference between this comparative example and Example 3-1 is that: in the preparation of the SiO2 hydrosol-based antibacterial agent in this comparative example, chitosan / nano-elemental silver composite antibacterial agent is used to replace chitosan / micron-elemental silver composite antibacterial agent, and the remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1. Among them, nano-elemental silver is prepared by conventional methods, and then chitosan / nano-elemental silver composite antibacterial agent is prepared by step 2 in Example 2-1.

[0107] Comparative Examples 1-8

[0108] The difference between this comparative example and Example 3-1 is that the fabric preparation method of this comparative example does not include step (1) in Example 3-1, that is, this comparative example does not perform surface modification treatment on the fiber. The remaining steps of this comparative example are basically the same as those of Example 3-1.

[0109] Results and Discussion

[0110] (1) Fiber surface modification effect test

[0111] The fiber modified fabrics prepared in Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-3 were tested for the terminal carboxyl content and weight loss rate as follows. The terminal carboxyl content was tested by the method described on page 13 of the patent specification of Application No. 200580018511.5, entitled Method for Modifying Polyamide; the weight loss rate was tested by the constant temperature dry weight method, which is as follows: the fabric was dried in an oven at 105-110°C until constant weight balance (about 4 hours), and the weight was measured using an analytical balance, weight loss rate = (W0-W1) / W0×100%, where: W0 is the weight of the fabric before treatment; W1 is the weight of the fabric after treatment. The test results of the modification effect are shown in Table 1 below:

[0112] Table 1 Test results of fiber surface modification effect

[0113] Terminal carboxyl content (mmol / kg) Weight loss rate / % Example 1-1 95.2 1.2±0.3 Example 1-2 101.1 1.3±0.3 Examples 1-3 97.2 1.2±0.3 Comparative Example 1-1 88.6 1.1±0.3 Comparative Example 1-2 83.5 0.8±0.3 Comparative Examples 1-3 84.3 2.0±0.3

[0114] The test results in Table 1 show that the terminal carboxyl content of the fiber treated in the example is significantly higher than that of the fiber treated in the comparative example. The terminal carboxyl content of the fiber treated in Example 1-1 is higher than that of the fiber treated in the comparative example 1-1, indicating that the addition of the nonionic surfactant increases the hydrolysis rate of the amide bond. The terminal carboxyl content of the fiber treated in Example 1-2 is the highest because the mass concentration of the protease in Example 1-2 is high, and there are more effective contact opportunities between the fiber and the biological enzyme per unit time.

[0115] The terminal carboxyl content of the fiber treated in Comparative Example 1-1 is higher than that of the fiber treated in Comparative Example 1-2 and Comparative Example 1-3. This may be because the pH value of the treatment solution of Comparative Example 1-1 is within the optimal active pH range of papain, so the terminal carboxyl content of the fiber treated in Comparative Example 1-1 is the highest among the fibers treated in the comparative examples. In addition, compared with Comparative Example 1-2 and Comparative Example 1-3, the terminal carboxyl content of the fiber treated in Comparative Example 1-3 is slightly higher. This may be because the pH value of the treatment solution of Comparative Example 1-3 is relatively low (pH=2.8). The stronger the acidity, the worse the stability of the amide bond. The weight loss rate of the fiber treated in the comparative example shows that the weight loss of the fiber is caused by the combined action of acidity and protease. The terminal carboxyl content of the fiber treated in Comparative Example 1-1 is the largest, but the weight loss rate is not the largest, indicating that the hydrolysis of the amide bond by the protease is more moderate than the hydrolysis of the amide bond by the acidic condition, so that the polyamide molecular chain will not be broken in a short time to generate small molecules and separate from the fiber body.

[0116] (2) Antibacterial rate test

[0117] like Figure 3 As shown, the fabrics prepared in Examples 3-1 to 3-3 and Comparative Examples 1-4 to 1-7 were tested for antibacterial rate; the test method for antibacterial rate was based on GB / T20944.1-2007 Evaluation of antibacterial properties of textiles Part 1: Agar plate diffusion method. The test results of antibacterial rate are shown in Table 2 below:

[0118] Table 2 Antibacterial rate test results

[0119]

[0120] The test results in Table 2 show that when alkyl polysiloxane hydrosol is used as the matrix, the antibacterial property of chitosan is the worst (Comparative Examples 1-6), the antibacterial property of micron elemental silver (Comparative Examples 1-4) and the antibacterial property of nano elemental silver (Comparative Examples 1-5) both reach 100%, and elemental silver can significantly improve the antibacterial property of chitosan. The antibacterial property of chitosan / micron elemental silver (Example 3-1, Example 3-2 and Example 3-3) is similar to that of elemental silver (Comparative Examples 1-4 and Comparative Examples 1-5), and is better than the antibacterial property of chitosan / nano elemental silver (Comparative Example 1-7). Cause analysis: Chitosan is a porous material. When elemental silver is compounded with chitosan, part of the elemental silver is adsorbed on the surface of chitosan, and the other part is adsorbed into the pores of chitosan. The smaller the particle size of elemental silver, the greater the probability of adsorption into the pores of chitosan. Elemental silver is a contact antibacterial agent, so the antibacterial property of chitosan / micron elemental silver (Example) is better than that of chitosan / nano elemental silver (Comparative Examples 1-7).

[0121] (3) Durability test

[0122] The fabrics prepared in Examples 3-1 to 3-3 and Comparative Examples 1-8 were tested for antibacterial rate, hand feel and static contact angle as follows, wherein the test method for antibacterial rate refers to GB / T20944.1-2007 Evaluation of antibacterial properties of textiles Part 1: Agar plate diffusion method; the hand feel test adopts the hand touch method; the static contact angle test adopts OCA50Micro fully automatic single fiber contact angle measuring instrument (German Dataphysics Instrument Co., Ltd.); the washing method refers to GB / T8629-2017 Household washing and drying procedures for textile testing. The test results are shown in Table 3 below:

[0123] Table 3 Test results

[0124]

[0125] The test results in Table 3 show that when the polyamide fabric is finished with a polyalkylsiloxane hydrosol-based antibacterial agent, the antibacterial property, feel and static contact angle of the fabric prepared in Comparative Examples 1-8 (without bioenzyme modification) are similar to those of the fabric prepared in Example 3-1 (bioenzyme modified), but after 20 or 50 washes, the various properties of the fabric prepared in Example 3-1 are significantly better than those of the fabric prepared in Comparative Examples 1-8. The main reason is that bioenzyme modification can not only form carboxyl groups (-COOH) on the fiber surface that are valence-bonded with silanol groups (Si-OH), but also form a microscopic rough structure. The rough structure produces a mechanical meshing effect with the polyalkylsiloxane coating, thereby improving the durability of the finishing effect.

[0126] Table 3 also shows that changing the polyalkylsiloxane precursor (i.e., the specific substance of alkylsiloxane) can give the finished fabric a different feel (Example 3-1, Example 3-2, and Example 3-3), but will not affect the antibacterial property (i.e., antibacterial rate) and hydrophobicity (i.e., static contact angle), nor will it have a significant effect on the durability of the finishing effect.

[0127] In the preparation method of the present invention, when modifying the fiber, the pH of the system is controlled to be about 3.5. The acidity at this time has a synergistic effect with the stripping of the polyamide fiber surface by the protease. The stripped fiber can not only effectively increase its adsorption amount of the polyalkylsiloxane hydrosol, but also improve the durability of the effect through mechanical anchoring and valence bond bonding (-COOH on the fiber and -OH on the polyalkylsiloxane). At the same time, the film formed by the polyalkylsiloxane can compensate for the damage caused by the stripping effect.

[0128] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fabric, characterized in that: The method comprises the following steps: modifying the fibers of the fabric by using protease under acidic conditions, and ensuring that the pH value of the system is always 3.0-4.0 during the modification process; then preparing a polyalkylsiloxane hydrosol; finishing the modified fabric by using the polyalkylsiloxane hydrosol to obtain the fabric; the surfactant used in the process of preparing the polyalkylsiloxane hydrosol is a mixture of sodium dodecylbenzene sulfonate and twain-80; the surfactant is a mixture of sodium dodecylbenzene sulfonate and twain-80 in a mass ratio of 1:0.1-0.3; The preparation of the polyalkylsiloxane hydrosol comprises the following steps: adding hydrochloric acid to deionized water, then adding a surfactant and a defoamer, stirring to fully dissolve and mix the surfactant, adding alkylsiloxane while stirring, and after the alkylsiloxane is added, continuing to stir and heating to 40-60° C., reacting for 30-60 minutes under stirring to obtain the polyalkylsiloxane hydrosol; An antibacterial agent is also added during the preparation of the polyalkylsiloxane hydrosol, wherein the antibacterial agent is a chitosan / micron elemental silver composite antibacterial agent; The preparation of the chitosan / micron elemental silver composite antibacterial agent comprises the following steps: Add chitosan with a mass concentration of 2-5% and acetic acid with a mass concentration of 1.0-2.0% to deionized water; 0.1-0.2% sodium dodecylbenzene sulfonate and ethanol are added into deionized water, stirred, and after the sodium dodecylbenzene sulfonate is completely dissolved, 5-10% of micron elemental silver is added to the chitosan mass while stirring to precipitate a micron elemental silver crude product, and then washed with deionized water to obtain micron elemental silver; Under the condition of 25-30°C, stir and add the micron elemental silver dispersion into the chitosan solution within 10-20 minutes. After the addition, continue stirring to precipitate a crude chitosan / micron elemental silver composite antibacterial agent, wash with deionized water, and filter to obtain the chitosan / micron elemental silver composite antibacterial agent.

2. The preparation method according to claim 1, characterized in that: The acidic condition has a pH value of 3.0-4.

0.

3. The preparation method according to claim 1, characterized in that: A buffer solution is used in the process of modifying the fibers of the fabric, wherein the buffer solution is a mixture of 0.1-0.3 mol / L disodium hydrogen phosphate and 0.0.5-0.2 mol / L citric acid.

4. The preparation method according to claim 2, characterized in that: The pH value of deionized water is adjusted to 3.0-4.0 with a buffer solution, and then protease is added, and the concentration of the protease in the system is 0.02-2.0 g / mL; the fabric is treated under the condition of a bath ratio of 1:25-35, and then the fabric is washed and dried.

5. The preparation method according to claim 1 or 4, characterized in that: The protease is papain.

6. The preparation method according to claim 1, characterized in that: Finishing the modified fabric includes the following steps: adjusting the pH value of the polyalkylsiloxane hydrosol to 6-7 with an alkali agent, finishing the modified fabric with a padding method, and then washing and drying to prepare the fabric.

7. A fabric prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for preparing nylon surface grafting chitosan hydrophilic antibiotic material

    CN101880403A

  • A method for preparing a durable antibacterial polyamide fabric

    CN111809385B

  • Manufacturing method of efficient antibacterial polyamide fabric

    CN111826952A

  • Method for modifying polyamide

    CN1965124A

  • An enzyme treating liquid used for improving hydrophilicity of nylon and a preparing method thereof

    CN104313890A